COMPARISON OF VIDEO CALL INSTRUCTIONS AND VOICE CALLS IN INDONESIAN LANGUAGE ON CHEST COMPRESSION ONLY HAND POSITION - Maulidah; Ruri Virdiyanti; Abdurahman Wahid; Emelia Rahmawati (Nurse and Health)
Background: Out of Hospital Cardiac Arrest (OHCA) or cardiac arrest events that occur outside the hospital are the focus of world health problems which is often threaten a person's life. First aid that must be given quickly and precisely is Cardio Pulmonary Resuscitation (CPR). The rapid initiation of CPR with correct hand positioning by laypersons in cases of OHCA is critical for improving survival rates.